2019
DOI: 10.3233/jad181028
|View full text |Cite
|
Sign up to set email alerts
|

Is Alzheimer’s Disease Risk Modifiable?

Abstract: Population-based clinic-pathological studies have established that the most common pathological substrate of dementia in community-dwelling elderly people is mixed, especially Alzheimer’s disease (AD) and cerebrovascular ischemic disease (CVID), rather than pure AD. While these could be just two frequent unrelated comorbidities in the elderly, epidemiological research has reinforced the idea that mid-life (age < 65 years) vascular risk factors increase the risk of late-onset (age ≥ 65 years) dementia, and spec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
59
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 96 publications
(84 citation statements)
references
References 290 publications
0
59
0
1
Order By: Relevance
“…In addition, among the effects of the three transgenes, sustained human Aβ production was shown to play a causal role in the peripheral metabolic impairments of 3xTg-AD mice. (24) The strong relation between type 2 diabetes and Aβ is well described in the literature (2,3) and is reflected in studies in animal models. Normal mice fed a long-term HFD accumulate cerebral Aβ, (30,36) while streptozotocin-induced diabetic mice also accumulate cerebral Aβ and develop memory dysfunction.…”
Section: Hepatic Aβ Clearance Is Decreased In Obese 3xtg-ad Micementioning
confidence: 87%
See 1 more Smart Citation
“…In addition, among the effects of the three transgenes, sustained human Aβ production was shown to play a causal role in the peripheral metabolic impairments of 3xTg-AD mice. (24) The strong relation between type 2 diabetes and Aβ is well described in the literature (2,3) and is reflected in studies in animal models. Normal mice fed a long-term HFD accumulate cerebral Aβ, (30,36) while streptozotocin-induced diabetic mice also accumulate cerebral Aβ and develop memory dysfunction.…”
Section: Hepatic Aβ Clearance Is Decreased In Obese 3xtg-ad Micementioning
confidence: 87%
“…All of these conditions present with cognitive impairment, and their presence in midlife is recognized a risk factor for later development of Alzheimer's disease (AD), the most common cause of dementia. (2,3) NAFLD is independently associated with lower cognitive performance, (4) affecting different types of memory. Patients with NAFLD exhibit difficulty with delayed memory recall, assessed by the Montreal Cognitive Assessment Test (5) and lower performance in the Serial Digit Learning Test, (6) as compared with healthy controls.…”
mentioning
confidence: 99%
“…While non-pharmacological interventions can improve cognition and delay progression of mild cognitive impairment (MCI) to dementia, and in some cases may be as or more effective than pharmacological approaches, heterogeneity of subjects and variability in interventions and outcomes continued to limit firm conclusions [11][12][13][14][15][16][17][18]. Interpretation is further confounded with non-pharmacological approaches since participants are typically not naïve to treatments and participants may have inherent deficiencies in metabolism or differential absorptive capacity of nutrients [4].…”
mentioning
confidence: 99%
“…Conversely, this study showed that the mean change in MPI in participants without smoking history was smaller by 1.87 than that in participants with smoking history, indicating that MPI longitudinally remained constant in participants with smoking history. According to several preceding studies, smoking is considered a risk factor for AD [22] , [23] , [24] . Owing to the lack of consensus in results between the present and previous reports, future studies are warranted investigating the involvement of other factors conferring protection against dementia in the participants with smoking history.…”
Section: Discussionmentioning
confidence: 99%